A visualidade e a oralidade na escrita de Waly Salomão - Augustto Correa Cipriani (2017)
This dissertation aims at investigating the visuality and orality in the work of Waly Salomão. Having as scope his poems, songs and babilaques until the mid-1980s, this study focus on understanding the ways in which the body presents itself in Salomãos writing, regarding counterculture as a historical moment. As for the research of visuality in Waly Salomãos writing, the study develops in three main axes: the approximation between the visual arts and his works; the analysis of calligraphy and typography in his texts; and the visual solutions when transposing lyrics into the book Gigolô de Bibelôs. Finally, in what concerns the mechanics of orality, firstly, two central terms in Waly Salomãos poetics that evoke considerations on orality, babilaque and algaravia, are discussed; later, the mechanics of orality and vocality in his writing are mapped; and, finally, the relations between orality and musicality present in his poetics are exposed.